Nexus between Foreign Remittances and Economic Growth in Nigeria: Role of the Financial Sector - Garba, Kassey P.; Adekunle, Wasiu; Adeniyi, Oluwatosin (Asian Journal of Economics and Empirical Research, 2020)
In recent times, the economic growth literature is becoming more interested in the macroeconomic impacts of foreign remittances. This focus could be because foreign remittances now constitute the largest source of foreign capital flows for developing countries next to foreign direct investment (FDI). To this end, the present study analyzed the possible role of the financial sector in the nexus between foreign remittances and economic growth in Nigeria over the period of 1981 to 2015. To circumvent the possible endogeneity problem among foreign remittances, financial development and economic growth, we employed the two-stage least squares (2SLS) technique. Unlike the previous findings, we offered new evidence that the complementarity or substitutability between foreign remittances and financial development in promoting Nigeria’s economic growth depends on the indicators of financial development used. We confirmed the complementary hypothesis in the case of the quantitative indicators of financial development, while we validated the substitutability hypothesis in favour of its qualitative measure. Both migrant workers and their beneficiaries should be encouraged to make use of banks so that foreign remittances could be made available to finance genuine investments. This could be possibly achieved through boosting the confidence of migrant workers in the domestic financial system and by raising the deposit rate so as to entice the beneficiaries to save a large chunk of remittances received.